2020
DOI: 10.1136/bjophthalmol-2020-317327
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning for automated glaucomatous optic neuropathy detection from ultra-widefield fundus images

Abstract: Background/AimsTo develop a deep learning system for automated glaucomatous optic neuropathy (GON) detection using ultra-widefield fundus (UWF) images.MethodsWe trained, validated and externally evaluated a deep learning system for GON detection based on 22 972 UWF images from 10 590 subjects that were collected at 4 different institutions in China and Japan. The InceptionResNetV2 neural network architecture was used to develop the system. The area under the receiver operating characteristic curve (AUC), sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 26 publications
0
28
0
Order By: Relevance
“…Eyes that truly had glaucoma were identified by glaucoma specialists who saw reproducible visual field scotomas that matched the appearance of the optic discs. Several other studies demonstrated that certain deep learning parameters can achieve high accuracy with AUC > 0.9 and sensitivity and specificity levels > 90%; false-positive and false-negative results were commonly due to pathologic myopia [65][66][67][68][69][70]. Even with the use of different fundus cameras, deep learning artificial intelligence was able to achieve an AUC > 0.9, provided that image augmentation was performed [71].…”
Section: Artificial Intelligencementioning
confidence: 99%
“…Eyes that truly had glaucoma were identified by glaucoma specialists who saw reproducible visual field scotomas that matched the appearance of the optic discs. Several other studies demonstrated that certain deep learning parameters can achieve high accuracy with AUC > 0.9 and sensitivity and specificity levels > 90%; false-positive and false-negative results were commonly due to pathologic myopia [65][66][67][68][69][70]. Even with the use of different fundus cameras, deep learning artificial intelligence was able to achieve an AUC > 0.9, provided that image augmentation was performed [71].…”
Section: Artificial Intelligencementioning
confidence: 99%
“…Recently, artificial intelligence (AI) has been reported to attain a high level of accuracy in the automated detection of numerous diseases from clinical images 10 – 15 . In ophthalmology, a large number of studies developed deep learning-based systems that could accurately detect ocular diseases such as diabetic retinopathy, retinal detachment, and glaucoma 16 21 . However, eyelid tumors, particularly malignant ones, which need early detection and prompt referral, are not well investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that UWF fundus imaging is useful for diagnosing glaucoma [ 30 ], whereas others have shown that accurate glaucoma diagnosis can be achieved by combining UWF fundus imaging with DL methods [ 31 , 32 , 33 , 34 ]. However, no studies have shown the results of true-colour confocal scanning in the field of glaucoma, and this modality has only been used for the diagnosis of diabetic retinopathy and retinal diseases [ 35 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study conducted by our team, true-colour confocal scanning was found to be superior to UWF fundus imaging in detecting localised RNFL defects (early changes in glaucoma) when eye physicians manually evaluated images taken using both modalities [ 12 , 30 , 31 ]. It is widely known that a high false-positive rate is obtained when UWF fundus imaging is used to manually determine localised RNFL defects.…”
Section: Introductionmentioning
confidence: 99%